Mineral Trioxide Aggregate (MTA) Used in Primary Teeth : A Review of the Literature - Petplook, Narumol (Journal of Health Science of Thailand, 2018)
Mineral Trioxide Aggregate ( MTA) is a new material and approval by the US FDA in human pulpal therapy (since 1998). MTA has been reported to have superior biocompatibility, sealing ability and less cytotoxic than other materials currently used in pulpal therapy. This report is a review of MTA's composition, physical properties and clinical used in primary teeth, as direct pulp capping and pulpotomy.